Irish stewed - Logan, Kylie (Logan, Kylie. Ethnic eats mysteries., 2016)
After flopping as a personal chef to a Hollywood movie star, jobless Laurel Inwood finds herself humbled in Hubbard, Ohio, helping her aunt.--[4]Cover.